1999
DOI: 10.1128/jb.181.7.2307-2313.1999
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Organization in the cps Gene Clusters for Expression of Escherichia coli Group 1 K Antigens: Relationship to the Colanic Acid Biosynthesis Locus and the cps Genes from Klebsiella pneumoniae

Abstract: Group 1 capsules of Escherichia coli are similar to the capsules produced by strains of Klebsiella spp. in terms of structure, genetics, and patterns of expression. The striking similarities between the capsules of these organisms prompted a more detailed investigation of the cps loci encoding group 1 capsule synthesis. Six strains of K. pneumoniae and 12 strains of E. coli were examined. PCR analysis showed that the clusters in these strains are conserved in their chromosomal locations. A highly conserved blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 50 publications
3
73
0
Order By: Relevance
“…Despite the variety of bacterial exopolysaccharides, bacteria use a limited repertoire of assembly and secretion strategies, which are represented in E. coli (Whitfield & Roberts, 1999;Whitfield & Paiment, 2003;Whitfield, 2006). For this organism, two models have been proposed for the biosynthesis and assembly of the different types of capsules based on genetic and biochemical criteria, with the one proposed for the capsules of groups 1 and 4 being the most common among Gram-negative bacteria (Rahn et al, 1999;Whitfield, 2006;Whitfield & Larue, 2008). This mechanism is Wzy-dependent, in contrast to the mechanism for groups 2 and 3 capsules, which are assembled via ABC-transporterdependent pathways (Whitfield, 2006).…”
Section: Genes and Biosynthetic Pathways Related To The Production Ofmentioning
confidence: 99%
“…Despite the variety of bacterial exopolysaccharides, bacteria use a limited repertoire of assembly and secretion strategies, which are represented in E. coli (Whitfield & Roberts, 1999;Whitfield & Paiment, 2003;Whitfield, 2006). For this organism, two models have been proposed for the biosynthesis and assembly of the different types of capsules based on genetic and biochemical criteria, with the one proposed for the capsules of groups 1 and 4 being the most common among Gram-negative bacteria (Rahn et al, 1999;Whitfield, 2006;Whitfield & Larue, 2008). This mechanism is Wzy-dependent, in contrast to the mechanism for groups 2 and 3 capsules, which are assembled via ABC-transporterdependent pathways (Whitfield, 2006).…”
Section: Genes and Biosynthetic Pathways Related To The Production Ofmentioning
confidence: 99%
“…Previous studies in our laboratory identified a potential stem-loop structure in the intergenic region between wzc and wbaP (Rahn et al, 1999). To assess the ability of the relevant DNA fragments from E. coli B44 to terminate transcription, a number of constructs were made using a termination-probe vector, pHV100 (Peabody et al, 1989).…”
Section: A Stem-loop Structure Located In the Wzc-wbap Intergenic Regmentioning
confidence: 99%
“…Genes early in the cluster are necessary for high-level polymerization and surface assembly of the CPS and include wza (an outer membrane lipoprotein), wzb (an acid phosphatase) and wzc (an inner membrane tyrosine autokinase) (Drummelsmith and Whitfield, 2000;Wugeditsch et al ., 2001). The wza , wzb and wzc genes are conserved in many other organisms that produce group 1-like polymers, including colanic acid in E. coli K-12 (Stevenson et al ., 1996), exopolysaccharide in Erwinia amylovora (Bugert and Geider, 1995) and capsule in Klebsiella pneumoniae (Arakawa et al ., 1995;Rahn et al ., 1999), indicating a conserved pathway for the surface expression of these polysaccharides. An examination of a number of capsule clusters from K. pneumoniae and E. coli has shown that the operons are highly conserved not only in organization, but also in nucleotide sequence between homologous genes, particularly wza , wzb and wzc .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations